2017
DOI: 10.1091/mbc.e16-09-0643
|View full text |Cite
|
Sign up to set email alerts
|

NEK7 is required for G1 progression and procentriole formation

Abstract: As cells exit mitosis, the decision to commit to the next cell cycle is made during G1. Not only DNA replication, but also centriole duplication is initiated as cells enter the S-phase. The kinase NEK7 is required for the timely regulation of G1 progression, S-phase entry, and procentriole formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 70 publications
2
14
0
Order By: Relevance
“…Indeed, similar phenotypes were generated by expression of a constitutively active NEK7, but not NEK6, kinase. These findings are consistent with growing evidence that NEK7 has microtubule-associated functions in interphase cells, with endogenous NEK7 localizing to the centrosome and depletion interfering with interphase microtubule dynamics, the centrosome duplication cycle and ciliogenesis 40,41,42,43,44 . Of particular interest to our findings, a kinasedependent role was recently described for NEK7 in stimulating dendrite growth in post-mitotic neurons.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, similar phenotypes were generated by expression of a constitutively active NEK7, but not NEK6, kinase. These findings are consistent with growing evidence that NEK7 has microtubule-associated functions in interphase cells, with endogenous NEK7 localizing to the centrosome and depletion interfering with interphase microtubule dynamics, the centrosome duplication cycle and ciliogenesis 40,41,42,43,44 . Of particular interest to our findings, a kinasedependent role was recently described for NEK7 in stimulating dendrite growth in post-mitotic neurons.…”
Section: Discussionsupporting
confidence: 89%
“…However, this study did not find evidence for a role of NEK7 in centriole duplication, in contrast to previous studies ( Kim et al, 2011 ). However, in a recent study, a detailed investigation still showed the important impact of NEK7 depletion on contributions to centrosomal accumulation of the APC/C cofactor Cdh1, which negatively regulates centriole duplication ( Gupta et al, 2017 ). Later, RGS2 was reported to be a novel interactor of NEK7.…”
Section: Nek7 In the Regulation Of Mitosismentioning
confidence: 99%
“…Indeed, both Nek6 and Nek7 are capable of directly phosphorylating microtubules in vitro (O'Regan and Fry, 2009 ). Furthermore, Nek6 and Nek7 have been implicated in regulation of centrosome duplication and maturation, senescence and the DNA damage response, all of which primarily take place in interphase (Lee et al, 2008 ; Jee et al, 2010 ; Kim et al, 2011 ; Gupta et al, 2017 ; Tan et al, 2017 ). Unexpectedly, Nek7 was found to be necessary for activation of the NLRP3 inflammasome, a multiprotein complex that activates inflammatory caspases in macrophages (He et al, 2016 ; Schmid-Burgk et al, 2016 ; Shi et al, 2016 ).…”
Section: Nek Kinases In Spindle Assemblymentioning
confidence: 99%